Enhancing Nursing and Pharmaceutical Care Management: A Comprehensive Literature Review - Dakhail, AL Enezi, Monawer; Sabbah, AL Enezi, Sultan; Nawi, AL Rawaili, Faleh; Swayed, AL Rawili, Sultanah; Alwan, AL Enezi, Khalaf; Mohammed, AL Enezi, Abdullah; Moharb, AL Rowili, Monawer (Journal of Ecohumanism, 2024)
This literature review explores strategies to enhance nursing and pharmaceutical care management, emphasizing their critical roles in healthcare delivery and patient outcomes. The review analyzes recent studies (2016–2024) to identify challenges, best practices, and emerging trends in these fields. Key findings highlight the importance of patient-centered approaches, interdisciplinary collaboration, and the integration of technology, such as telemedicine and AI, in improving care quality and efficiency. Challenges like workforce shortages, training gaps, and resource limitations are examined, alongside solutions for bridging these gaps. The review provides actionable recommendations for healthcare administrators, practitioners, and policymakers to improve care delivery and foster collaboration between nursing and pharmaceutical teams. This work underscores the need for continuous innovation and research to address evolving healthcare demands and enhance patient safety and satisfaction.